The Explanatory Efforts of the Scholar Shabeer Ahmed Al-Othmani (1369 AH) in his Book Fateh Al-Mulhim with the Explanation of Sahih Muslim for his Interpretation of Some Meccan Verses from Surat Al-An’am and Al-Araf as a Model_a Comparative Study (Islamic Sciences Journal, 2023)
ABSTRACT                              The research aims to highlight the explanatory efforts of the scholar Shabeer Ahmed Al-Othmani in his book: Fateh Al-Mulhim with the explanation of Sahih Muslim. Despite the fact that the book is specialized in the science of hadith, the Mark Shabeer had explanatory pauses in a brief and clear phrase, and from here came this research marked with (interpretive efforts of the sign Shabeer Ahmed Al-Othmani in his book Fateh Al-Mulhim with the explanation of Sahih Muslim for his interpretation of some Meccan verses - from Surat Al-An’am and Al-A’raf as a model).
Keywords: Shabeer, his scientific life, his death, the interpretation of the verses, his efforts.